Practical collider physics - Buckley, Andy (Ph. D. in particle physics); White, Christopher D.(Ph. D. in physics); White, Martin John (IOP (Series). Release 21., 2021)
Practical Collider Physics provides a self-contained summary of all of the necessary theoretical, experimental and statistical knowledge required to analyse hadron collider data, focussing on the skills and techniques that are rarely covered in standard textbooks. It covers topics including parton distribution functions, resummation, parton showers, hadronisation, and the underlying event and jet algorithms, all of which are vital for understanding the form and function of Monte Carlo generators.